Are Restrictive Medical Radiation Imaging Campaigns Misguided? It Seems So: A Case Example of the American Chiropractic Association’s Adoption of “Choosing Wisely” - Paul A. Oakley; Deed E. Harrison (Dose-Response, 2020)
Since the 1980s, increased utilization of medical radiology, primarily computed tomography, has doubled medically sourced radiation exposures. Ensuing fear-mongering media headlines of iatrogenic cancers from these essential medical diagnostic tools has led the public and medical professionals alike to display escalating radiophobia. Problematically, several campaigns including Image Gently, Image Wisely, and facets of Choosing Wisely propagate fears of all medical radiation, which is necessary for the delivery of effective and efficient health care. Since there are no sound data supporting the alleged risks from low-dose radiation and since there is abundant evidence of health benefits from low-doses, these imaging campaigns seem misguided. Further, thresholds for cancer are 100 to 1000-fold greater than X-rays, which are within the realm of natural background radiation where no harm has ever been validated. Here, we focus on radiographic imaging for use in spinal rehabilitation by manual therapists, chiropractors, and physiotherapists as spinal X-rays represent the lowest levels of radiation imaging and are critical in the diagnosis and management of spine-related disorders. Using a case example of a chiropractic association adopting “Choosing Wisely,” we argue that these campaigns only fuel the pervasive radiophobia and continue to constrain medical professionals, attempting to deliver quality care to patients.